DIFFERENTIAL DIAGNOSTICS OF THE VESICO-VASCULAR SYNDROME OF THE ORAL MUCOSA - T.P. Skripnikova; L.Ya. Bogashova; Т.А. Khmil (Ukrainian Medical Stomatological Academy, 2017)
According to the literature, the pathogenesis of vesico-vascular syndrome in the pathology of cardiovascular activity is adequately covered. However, there are difficulties in differential diagnosis. The aim of the work is to deepen the differential diagnosis of diseases of the oral mucosa accompanied by a vesico-vascular syndrome. Observations were carried out on 8 patients with vesico-vascular syndrome, of which 2 men (25%) and 6 women (75%) at the age of 55-67 years who suffered from hypertension. As a result of analysis of literature data, differential diagnosis and own research, it can be concluded that vesico-vascular syndrome is accompanied by the following triad of symptoms: cardiovascular insufficiency, which arises as a complication of hypertension; increased permeability of arterial blood vessels, fragility of the vascular wall, conducive to the formation of blisters; positive symptom of peripheral detachment.